The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1055/s-0038-1676487
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Preterm Birth among Women of Native Hawaiian and Pacific Islander Descent

Abstract: Objective To describe the characteristics and risk factors for preterm birth in Hawaiian and Pacific Islander women. Study Design Retrospective cohort study of 10,470 women of Hawaiian or Pacific Islander descent drawn from a population-based birth cohort dataset in California. Variables were examined across preterm birth subtype (spontaneous, provider initiated) and by gestational age grouping (early preterm birth and late preterm birth) and all preterm births. Results Hawaiian/Pacific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Using the same screening approach, we selected three new articles for analysis (Figure 1). After removing potentially overlapping data from different sources (for example, if studies reported data collection using the same data source, with overlapping timelines), a total of 14 studies [41][42][43][44][45][46][47][48][49][50][51][52][53][54] were included in the meta-analyses presented here. Two 53,54 of the 14 studies were identified through the gray literature search.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the same screening approach, we selected three new articles for analysis (Figure 1). After removing potentially overlapping data from different sources (for example, if studies reported data collection using the same data source, with overlapping timelines), a total of 14 studies [41][42][43][44][45][46][47][48][49][50][51][52][53][54] were included in the meta-analyses presented here. Two 53,54 of the 14 studies were identified through the gray literature search.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the included studies are presented in Table 1 ordered by the starting year of data collection, which occurred between 1989 and 2018. Of the 14 included studies, 10 (71.4%) studies 43,44,46,47,[49][50][51][52][53][54] reported PTB prevalence among Pacific Islanders, eight (57.1%) studies 42,44,46,47,49,50,53,54 were used to estimate risk of PTB compared with white women, and only 2 (14.3%) studies 48,52 reported risk factors (hypertension, diabetes, smoking during pregnancy, and weight status [underweight, overweight, or obesity]) for PTB in Pacific Islander-specific analyses. Smoking before pregnancy was not reported.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to trimester-averaged exposure models, these studies have reported inconsistent findings and no clear etiologically relevant period of susceptibility has been identified. For example, studies have reported susceptible windows during both early and late gestation [31], early gestation only [32], middle gestation only [11], late gestation only [33], early and middle gestation [10], middle and late gestation [34], or have failed to identify any susceptible window [35,36]. A notable limitation of prior studies with high temporal resolution is that spatial resolution has been limited, with PM 2.5 exposure typically estimated at the zip code or county level using ground monitoring data.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-pregnancy BMI is related to the birth weight of the child and complications during pregnancy 2 . There is an increased risk of low birth weight 38 , foetal growth restriction (FGR) 4,5,9 , threatened preterm delivery, and preterm delivery 3,4,6,10 , and anaemia 3,11 in pre-pregnant underweight women when compared with those with normal weight before pregnancy. A meta-analysis 12 reported that women who gain less weight than that recommended by the Institute of Medicine (IOM) during pregnancy have increased risk of preterm delivery and small-for-gestational age (SGA) infants, while women who gain more weight than that recommended have an increased risk of foetal macrosomia, caesarean delivery, and large-for-gestational age (LGA) infants.…”
Section: Introductionmentioning
confidence: 99%